Modelling of Neuronal Ceroid Lipofuscinosis Type 2 in Dictyostelium discoideum Suggests That Cytopathological Outcomes Result from Altered TOR Signalling - Paige K. Smith; Melodi G. Sen; Paul R. Fisher; Sarah J. Annesley (Cells, 2019)
The neuronal ceroid lipofuscinoses comprise a group of neurodegenerative disorders with similar clinical manifestations whose precise mechanisms of disease are presently unknown. We created multiple cell lines each with different levels of reduction of expression of the gene coding for the type 2 variant of the disease, Tripeptidyl peptidase (Tpp1), in the cellular slime mould Dictyostelium discoideum. Knocking down Tpp1 in Dictyostelium resulted in the accumulation of autofluorescent material, a characteristic trait of Batten disease. Phenotypic characterisation of the mutants revealed phenotypic deficiencies in growth and development, whilst endocytic uptake of nutrients was enhanced. Furthermore, the severity of the phenotypes correlated with the expression levels of Tpp1. We propose that the phenotypic defects are due to altered Target of Rapamycin (TOR) signalling. We show that treatment of wild type Dictyostelium cells with rapamycin (a specific TOR complex inhibitor) or antisense inhibition of expression of Rheb (Ras homologue enriched in the brain) (an upstream TOR complex activator) phenocopied the Tpp1 mutants. We also show that overexpression of Rheb rescued the defects caused by antisense inhibition of Tpp1. These results suggest that the TOR signalling pathway is responsible for the cytopathological outcomes in the Dictyostelium Tpp1 model of Batten disease.